2020
DOI: 10.3389/fncel.2020.603043
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Basis of Intracerebral Hemorrhage and Cell Toxicity With Contributions From Eryptosis and Ferroptosis

Abstract: Intracerebral hemorrhage (ICH) is a particularly devastating event both because of the direct injury from space-occupying blood to the sequelae of the brain exposed to free blood components from which it is normally protected. Not surprisingly, the usual metabolic and energy pathways are overwhelmed in this situation. In this review article, we detail the complexity of red blood cell degradation, the contribution of eryptosis leading to hemoglobin breakdown into its constituents, the participants in that proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 206 publications
(306 reference statements)
0
17
0
Order By: Relevance
“…In addition to CD47, another scavenger protein, CD36, a well-recognized integral microglia/macrophage cell membrane protein, is involved in the activation of phagocyte-mediated innate immune responses in ICH ( Xia et al, 2022 ). The increase in CD36 expression in the perihematomal region is associated with faster hematoma clearance, and reduced CD36 expression increases the production of pro-inflammatory M1 macrophages/microglia mediators, such as TNF-α and IL-1β, thus inhibiting erythrophagocytosis and hematoma clearance ( Fang et al, 2014 ; Derry et al, 2020 ). As efferocytosis of eryptotic erythrocytes in HS is also a method of erythrophagocytosis of “abnormal” erythrocytes, the recognition of eryptotic erythrocytes by phagocytes is dependent on Ca 2+ -induced PS exposure on the erythrocyte outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CD47, another scavenger protein, CD36, a well-recognized integral microglia/macrophage cell membrane protein, is involved in the activation of phagocyte-mediated innate immune responses in ICH ( Xia et al, 2022 ). The increase in CD36 expression in the perihematomal region is associated with faster hematoma clearance, and reduced CD36 expression increases the production of pro-inflammatory M1 macrophages/microglia mediators, such as TNF-α and IL-1β, thus inhibiting erythrophagocytosis and hematoma clearance ( Fang et al, 2014 ; Derry et al, 2020 ). As efferocytosis of eryptotic erythrocytes in HS is also a method of erythrophagocytosis of “abnormal” erythrocytes, the recognition of eryptotic erythrocytes by phagocytes is dependent on Ca 2+ -induced PS exposure on the erythrocyte outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed the biodegradation of hemoglobin into multiple toxic by-products, including hemin, as the primary contributing factor in eryptosis and ferroptosis ( Derry et al, 2020 ). We further provided evidence that hemin can cause direct DNA double-strand breaks (DSBs) in the genome, the most lethal form of genome damage, in both endothelial and neuronal cells ( Dharmalingam et al, 2020 ).…”
Section: Sars-cov-2-induced Thrombosis Hemolysis and Microbleedsmentioning
confidence: 99%
“…Cerebral hemorrhage-derived hemin exposure can induce the expression of Toll-like receptor 4 (TLR4) signaling, which in turn activates pro-inflammatory factors, like IL-6 and phosphorylated STAT3. Upregulation of these factors has been correlated with progressive cognitive impairment in hemorrhagic stroke survivors ( Derry et al, 2020 , Xiong et al, 2016 ). Moreover, studies have shown the effects of cytokine storms in inducing a senescent stage, along with the accumulation of oxidative DNA damage ( Ren et al, 2009 ).…”
Section: Sars-cov-2-induced Thrombosis Hemolysis and Microbleedsmentioning
confidence: 99%
“…After spinal cord injury, the spinal cord exhibits substantial hemorrhaging, erythrocyte aggregation, cell rupture, and hemolysis and local iron overload ( Derry et al, 2020 ). Moreover, stress induces the production of a large amount of ROS and increases the excitotoxicity of glutamate ( Kang et al, 2020 ).…”
Section: The Effect Of Ferroptosis On Tbi and Scimentioning
confidence: 99%
“…Reactive astrocytes, which are the major component of the glial scar and function as a chemical and physical barrier to axon regeneration, are associated with the failure of axon regeneration in individuals with SCI ( Patil et al, 2021 ). Deferoxamine (DFO), an iron chelator, is capable of suppressing ferroptosis triggered by the increase in the activity of the Xc – /GPX4 axis in SCI, and the antigliotic effect of DFO was consistent with its effect on GPX4 upregulation ( Derry et al, 2020 ). This result indicated a potential link between gliosis and ferroptosis following SCI, which requires further research.…”
Section: The Effect Of Ferroptosis On Tbi and Scimentioning
confidence: 99%